PENYULUHAN MENGENAI KONSERVASI EKOSISTIM PERAIRAN DAN PENATAAN LANSKAP BANTARAN SITU PANGARENGAN KOTA DEPOK - Fachrul, Melati Ferianita; Hendrawan, Diana; Rinanti, Astri; Besila, Qurrotu ‘Aini; Magfhira, Azzahra (JUARA: Jurnal Wahana Abdimas Sejahtera, 2023)
Damage to the ecosystem there will cause problems for the city. The factors causing the damage to the lake in Depok City are changes in land use in the catchment area, sedimentation, pollution and eutrophication resulting in reduced aesthetic value. Basically, this lake ecosystem can be turned into a tourist destination. Situ Pangarengan, which is located in Cisalak Village, Sukma Jaya District, Depok City, initially has an area of about 10.00 Ha, but now it is 8.00 Ha and shrinks in the dry season to 6.70 Ha. Therefore, saving this ecosystem needs to be done by conducting outreach to the people who live around it. The purpose of this activity is to provide counseling on management by implementing conservation and structuring the landscape along Situ Pangarengan. The activity was carried out on August 18, 2022, attended by 40 people. The PKM method is carried out with counseling in the form of lectures, discussions. The training atmosphere is designed to be interactive so that participants can more easily understand with case examples in the field. The results of this PkM activity participants gain knowledge about the benefits of managing and conserving the Situ Pangarengan ecosystem properly; participants get information about the landscape design for the lake bank; participants get a forum to exchange opinions and provide input regarding the management of the Situ Pangarengan ecosystem and the necessary communication occurs between extension workers and participants for the preparation of further action plans